Mechanisms and implications of antibiotic resistance in gram-positive bacterial strains: Antibiotic resistance in gram-positive bacterial - Naifa Alenazi (Cellular and Molecular Biology, 2025)
Antibiotics play a fundamental role in protecting millions of lives from infectious diseases. However, an important drawback of antibiotic treatment is that each advancement was followed by the development of resistance. This is due to the fact that the majority of pathogenic bacteria are capable of becoming resistant to a number of antimicrobial agents. There are a number of resistance mechanisms the microorganism may possess naturally or by acquisition from other microorganisms. The main mechanisms of resistance to a medication include altering its target, preventing its absorption, causing it to efflux actively, and rendering it inactive. Many types of gram-positive bacteria that cause serious infections in both the community and healthcare system are listed among the most dangerous bacteria according to the WHO’s published list, which calls for the development of novel antibiotics to address the resistance issue. The following three strains, methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus faecium, and penicillin-resistant Streptococcus pneumoniae, are of special importance. Therefore, this review highlighted the main mechanisms and consequences of antibiotic resistance in Gram-positive bacterial strains.